Detection of kpc-type Carbapenemases in Clinical Isolates of Acinetobacter baumannii - Hannan Khodaei; Fereshteh Eftekhar (Journal of Krishna Institute of Medical Sciences University, 2017)
Background: Multidrug-resistant Acinetobacter baumannii is associated with life threatening nosocomial infections and hospital outbreaks. The organism is resistant to most commonly used antibiotics including carbapenems. Aim and Objectives: To study carbapenemase production among multidrug-resistant clinical isolates of A. baumannii. Material and Methods: Fifty multidrug-resistant A. baumannii isolates were selected based on PCR identification of the bla gene. Minimum inhibitory OXA-51 concentrations were determined to imipenem and meropenem. Carbapenemase production was detected by the Modified Hodge Test (MHT) and the Combined Disc Method (CDM). Presence of the Klebsiella pneumoniae carbapenemases (KPC-2) type carbapenemase gene was shown by PCR using specific primers. Results: All isolates were resistant to imipenem and meropenem. MHT and CDM results showed carbapenemase production in 78% and 56% of the isolates, respectively. KPC-2 type gene was not observed in any of the isolates. Conclusion: No correlation was found between carbapenem susceptibility with phenotypic detection of carbapenemase production or KPC-type gene carriage.